Restructuring development theories and policies : a critical study - Haque, M. Shamsul (Albany, N.Y. : State University of New York Press, 1999)
"In the contemporary global context replete with various forms of development crises, there is a growing demand for an alternative perspective. Haque explains the nature and forms of these current development crises, critiques the inadequacies of existing development theories to address such crises, restructures these theories into an alternative theoretical perspective, and suggests specific policy guidelines for attaining a genuine mode of development. He interprets development not as human conformity with any hegemonic development schemes, but as human autonomy from various forms and levels of subjugation. The book presents original arguments, covers up-to-date literature, adopts a multidisciplinary approach, mediates between theories and policies, and offers a comprehensive development alternative."--BOOK JACKET.
Ch. 1. An Introductory Overview -- Ch. 2. Practical Crises of Development -- Ch. 3. A Taxonomic Prelude to Development Theories -- Ch. 4. Conservative Tradition of Development Theories -- Ch. 5. Reformist Tradition of Development Theories -- Ch. 6. Radical Tradition of Development Theories -- Ch. 7. A Critique of Development Theories -- Ch. 8. Restructuring Concepts and Theories of Development -- Ch. 9. Reforming Development Policies.
Includes bibliographical references and index.
Keywords: Economic development -- Case studies